2022
DOI: 10.3390/ijms23105591
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenia: A Narrative Review on Clinical Studies

Abstract: Osteosarcopenia (OS) is defined by the concurrent presence of osteopenia/osteoporosis and sarcopenia. The pathogenesis and etiology of OS involve genetic, biochemical, mechanical, and lifestyle factors. Moreover, an inadequate nutritional status, such as low intake of protein, vitamin D, and calcium, and a reduction in physical activity are key risk factors for OS. This review aims to increase knowledge about diagnosis, incidence, etiology, and treatment of OS through clinical studies that treat OS as a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 86 publications
0
29
1
4
Order By: Relevance
“…In the pathogenesis of peripheral fragility fractures, in addition to osteoporosis, sarcopenia is also of relevance [ 64 ]. In a recently published study, BMD and skeletal muscle mass were assessed in 549 patients with RA and 158 control subjects.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…In the pathogenesis of peripheral fragility fractures, in addition to osteoporosis, sarcopenia is also of relevance [ 64 ]. In a recently published study, BMD and skeletal muscle mass were assessed in 549 patients with RA and 158 control subjects.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…The dysregulation of this axis and GH decreased secretion leads to a decrease in muscle and bone mass and to an increase in adipose tissue accumulation. 52 Both muscle and bone cells express hormone receptors, making it clear how critical it is in postmenopausal women, where oestrogen decline occurs, to set up hormone replacement treatment to preserve bone and muscle mass and prevent future fragility fractures. 52 In addition, it has been shown that the decrease in circulating levels of estradiol in postmenopausal women has important effects on the state of bone and muscle tissue, leading to their decline.…”
Section: Bone-muscle Connection In Osmentioning
confidence: 99%
“…Vor allem Übungen mit dem eigenen Körpergewicht, Krafttraining und aerobes Ausdauertraining werden hier als nützlich diskutiert [5,80]. Im Rahmen der FrOST Studie (Franconian Osteopenia and Sarcopenia Trial) konnte dargestellt werden, dass Krafttraining zusammen mit einer Protein-Supplementierung einen positiven Effekt bezüglich Sarkopenie und Osteoporose hat, während eine Protein-Supplementierung ohne begleitendes Training diesbezüglich ineffektiv blieb [77,[81][82][83].…”
Section: Ernährung Und Trainingunclassified
“…Körperliche Aktivität stellt einen der grundlegenden Bausteine sowohl in der Prävention als auch der Therapie der Osteoporose und Sarkopenie dar. Mechanischer Stress führt zu einer Zunahme der Muskelmasse und erhöht die Aktivität der Osteoblasten 77 78 79 . Vor allem Übungen mit dem eigenen Körpergewicht, Krafttraining und aerobes Ausdauertraining werden hier als nützlich diskutiert 5 80 .…”
Section: Introductionunclassified